Investigating the Plant Species and Rainfall Factors on Stormwater Retention Performance of Extensive Green Roofs in Malaysia - Ming Fai, Chow; Fadhlullah Abu Bakar, Muhammad; Mohd Sidek, Lariyah; Khai, Wong Jee (International Journal of Engineering and Technology, 2018)
Information on the influences of native plant species and rainfall characteristics on the stormwater retention performance of extensive green roofs in Malaysia is still scarce. More local data is still required because rainfall and runoff generation processes in tropical environment are very different from the temperate regions. This study is aimed to investigate the stormwater retention performance of native plant species in extensive green roofs with respect to different rainfall characteristics in Malaysia. Two test beds consist of pro-mixing potting soil were vegetated each with different native plant species (Axonopus Compressus (cow grass), Portulaca Grandiflora (sedum) and one test bed with no vegetation (bare ground) was prepared as a control. A total of 22 significant storm events were collected over a 3-month period from March 2016 to May 2016. The rainfall depths for monitored storm events were ranged from 4.5 mm to 63.2 mm and rainfall intensities ranged from 0.5mm/hr to 58.5 mm/hr. The results showed that sedum exhibited higher mean runoff retention percentage than grass which is 75.8% and 70.9%, respectively. Bare soil was the least effective for reducing water runoff with retention percentage of 62.6%. Overall, sedum and grass species provided 90.6% and 88.2% of cumulative rainfall retention in this study. The rainfall depth and intensity are correlated negatively with stormwater retention performance of green roofs. Meanwhile, longer dry weather period are likely to increase the water retention capacity of green roof.Â Â